Using Black Feminist Theory and Methods to Uncover Best Practices in Health Promotion Programming. (February 2022) - Wade, Jeannette; Alexander, Ramine; Giscombé, Cheryl Woods; Keegan, Daniel; Parker, Sharon; Jackson, Katia; Gibbs, Jasmine; McElroy, Asha; Ferguson, Ja Vae
This study was created to uncover the social determinants of Black American women's success in health promotion programs. We used the Superwoman Schema to understand the complexities of Black womanhood and uncover best practices in the promotion of their health. The sample consisted of women ages 18–25 who attend a large southern HBCU. We collected data using qualitative focus groups. Participants reported the greatest health-related concerns Black American women facing are mental health, obesity, and relationships with Black men. When it comes to health promotion programs, respondents reported a desire for classes that are fun, interactive, informative, educational, and include group interaction, accessible, and incentivize participation. Uncovering the social determinants of Black American women's health and program success is central in decreasing extant health disparities. Future health scholars are urged to incorporate Black feminist theory and methods into their work to create health promotion interventions tailored for Black women.